Object-based learning and well-being : exploring material connections - Kador, Thomas; Chatterjee, Helen (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"'Object-Based Learning and Well-Being' provides the first explicit analysis of the combined learning and well-being benefits of working with material culture and curated collections. Following on from the widely acclaimed Engaging the Senses, this volume explicitly explores the connection between the value of material culture for both learning and well-being. Bringing together experts and practitioners from eight countries on four continents, the book analyses the significance of curated collections for structured cultural interventions that may bring both educational and well-being benefits. Topics covered include the role of material culture in relation to mental health; sensory impairments; and general student and teacher well-being. Contributors also consider how collections can be employed to positively address questions of identity and belonging relating to marginalisation, colonialism and forced displacement. 'Object-Based Learning and Well-Being' should be a key first point of reference for academics and students who are engaged in the study of object-based learning, museums, heritage, health and well-being. The book will be of particular interest to practitioners working in higher education, or those working in the cultural, heritage, museums and health sectors"--
Includes bibliographical references and index.
Keywords: Active learning -- Study and teaching (Higher).; Museums -- Educational aspects; Museums -- Psychological aspects; Object-teaching.